High-throughput screening of inhibitors of NMNAT1 and their tumor-targeting functions - SHA Wu-ga, LI Jun (Jichu yixue yu linchuang, 2022)
Objective To find new drug candidates for cancer treatment by screening inhibitors of NMNAT1 using recombinant human NMNAT1 expressed in E. coli system. Methods The human NMNAT1 was inserted into the pET21b(+) vector and the recombinant plasmid was transformed into E. coli BL21(DE3) strain for over expression of NMNAT1 protein. The enzymatic activity of NMNAT1 was measured by a three-step coupled fluorescence assay, and 2 280 chemicals from a nature compounds library were screened using this assay for potential inhibitors of NMNAT1. The potential target compounds that inhibited NMNAT1 were verified at the cellular level and tested for tumor-killing effect. Results The recombinant human NMNAT1 proteins with high purity and activity were obtained and 6 kinds of high-efficiency NMNAT1 inhibitors were identified. One of the them, fraxetin, efficiently reduced the NAD+ content of breast cancer cells and promoted cell apoptosis. RNA-seq analysis of NMNAT1 knock-down cells revealed the function to enhance apoptosis which is consistent with the cellular effect of NMNAT1 inhibitor. Conclusions Fraxetin is a high-efficiency NMNAT1 inhibitor to promote apoptosis of breast cancer cells.